1946
DOI: 10.1146/annurev.bi.15.070146.000343
|View full text |Cite
|
Sign up to set email alerts
|

Non-Oxidative Enzymes

Abstract: An extensive account of recent work on enzymes which hydrolyze the peptide linkage was given by Greenberg & Winnick in last year's Annual Review of Biochemistry (1). The present discussion of these enzymes is necessarily limited to a consideration of a relatively small number of contributions selected from the more recent literature.Plant proteinases.-To the list of these enzymes previously re corded (1) may now be added the pro teinase "arachain" which was isolated in purified form from the cotyledons and emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1948
1948
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…303 They synthesized two phosphotripeptides, Nap-GFF p Y-OMe ( 9) and Nap-Gff p y-OMe (11) (Figure 35A). After confirming the formation of hydrogels of Nap- GFFY-OMe (10) and Nap-Gffy-OMe (12), they used the hydrogels as vaccine adjuvants and found that both L-and Dpeptide hydrogels are more potent than the clinically used alum adjuvant in the increase of the IgG production of OVA. Notably, the OVA encapsulated D-peptide hydrogel exhibits a slightly more efficient accumulation of OVA in the lymph nodes for preventing tumor growth than the L-peptide hydrogel does.…”
Section: Enzymatic Noncovalent Synthesis In Cell-free Conditionsmentioning
confidence: 97%
See 2 more Smart Citations
“…303 They synthesized two phosphotripeptides, Nap-GFF p Y-OMe ( 9) and Nap-Gff p y-OMe (11) (Figure 35A). After confirming the formation of hydrogels of Nap- GFFY-OMe (10) and Nap-Gffy-OMe (12), they used the hydrogels as vaccine adjuvants and found that both L-and Dpeptide hydrogels are more potent than the clinically used alum adjuvant in the increase of the IgG production of OVA. Notably, the OVA encapsulated D-peptide hydrogel exhibits a slightly more efficient accumulation of OVA in the lymph nodes for preventing tumor growth than the L-peptide hydrogel does.…”
Section: Enzymatic Noncovalent Synthesis In Cell-free Conditionsmentioning
confidence: 97%
“…The study of enzymes started with the identification and categorization of enzymes more than 70 years ago. 9,10 The emphasis, then, has focused on the mechanisms of enzyme actions. 11−15 With the rapid advance of structural biology, researches over the last 40 years have elucidated the structures of many enzymes, especially their active sites.…”
Section: Enzymatic Covalent Synthesismentioning
confidence: 99%
See 1 more Smart Citation